Question

( frac{sec theta+tan theta}{sec theta-tan theta}=left(frac{1+sin theta}{cos theta}right)^{2} )
( frac{alpha cdot sec theta cdot sec theta+tan theta}{sec theta-tan theta} times frac{sec theta+tan theta}{sec theta+tan theta}=frac{(sec theta+tan alpha)^{2}}{sec ^{2} theta-tan ^{2} theta}=frac{left(sec ^{2} theta+tan thetaright)^{2}}{1 .}=(sec theta+tan theta)^{2} )
[
sin left(frac{1+operatorname{sen} theta}{cos theta}right)^{2}=(sec theta+tan theta)^{2}
]

# sec 0 + tan 0 Prove that sec 0 - tano (1 + sin ( cos ? )

Solution